The art of time travel historians and their craft - Griffiths, Tom 1957- (Black Inc., 2016)
No matter how practised we are at history, it always humbles us. No matter how often we visit the past, it always surprises us. The art of time travel is to maintain critical poise and grace in this dizzy space.' In this landmark book, eminent historian and award-winning author Tom Griffiths explores the craft of discipline and imagination that is history. Through portraits of fourteen historians, including Inga Clendinnen, Judith Wright, Geoffrey Blainey and Henry Reynolds, Griffiths traces how a body of work is formed out of a lifelong dialogue between past evidence and present experience. With meticulous research and glowing prose, he shows how our understanding of the past has evolved, and what this changing history reveals about us. Passionate and elegant, The Art of Time Travel conjures fresh insights into the history of Australia and renews our sense of the historian's craft
Keywords: Australian; Historiography / Australia; Historians / Australia; Historians; Historiography; Geschichte; Australia / History; Australia; Australien